Tamoxifen/Antioestrogens increase aggressiveness of breast cancer with HER-2 gene amplification and/or overexpression - Szacikowska, Ewa; Kozłowski, Wojciech (Contemporary Oncology/Współczesna Onkologia, 1999)
The aim of the paper is presentation of the results of the newest basic studies on hormonal reactivity of epithelial cells of human breast cancer with HER-2 gene amplification. These studies conducted on cell models unequivocally indicate the role of tamoxifen/antioestrogens in the processes connected with cell growth regulation. These studies demonstrate also that HER-2 gene, the product of which, p185 receptor protein, leads, in case of amplification of the gene, to significant proliferation increase of such cells and to rising of their metastatization potential, is the gene remaining under oestrogen control. In the presence of oestrogen receptors, oestradiol, in the cells with HER-2 gene amplification, leads to a reduction of transcript amount of this gene, while tamoxifen/antioestrogens intensify its transcription leading to increase of aggressiveness of such clone in tumour. This mechanism leads to the clinically observed, statistically significant shortening by tamoxifen/antioestrogens of the relapse-free time and overall survival time in comparison to control group of patients, also with HER-2 gene amplification but not subjected to antioestrogen treatment. Therefore, administration of antioestrogens to patients with breast cancer with HER-2 gene amplification is harmful. In the paper, clinical studies are presented from the last decade which are reports fully agreeing with the results of the most recent basic studies. Some of the papers already eight years ago shed proper light onto this problem but were given cold reception.